HTTP blocking in EG: instagram.com, signal.org, telegram.org, twitter.com, whatsapp.com (Egypt) - Voidly (2026)
WARNING severity censorship detected in Egypt. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: EG-2026-0004
Keywords: censorship; EG; censorship; warning